Gas Exchange and Leaf Anatomy of Cotton Subjected to Application of Calcium Silicate and Mepiquat Chloride under Water Stress - da Silva, Dayane Bortoloto [UNESP]; Paixão-Daruichi, Amanda Pereira [UNESP]; de Souza Vieira, Noemi Cristina [UNESP]; Martins, Aline Redondo [UNESP]; Furlani, Enes [UNESP] (Friends Science Publishers, 2023)
Silicate fertilization can give crops better conditions to withstand edaphoclimatic and biological adversities, with the result of increased production and better quality. The objective of this work was to study leaf anatomy and gas exchange in herbaceous cotton as a function of calcium silicate doses, mepiquat chloride (MC) use and water availability. The experiment was carried out in a greenhouse. The experimental design was completely randomized, in a 4 × 2 × 2 factorial design, with 4 replications. The factors studied were four doses of calcium silicate (CS) as foliar fertilizer at the rate of 0, 100, 200 and 400 g/ha with and without the foliar spray of MC. Two soil water levels i.e., full field capacity (FC) and 1/3 FC (water stress). The foliar spray of CS and MC increased net photosynthesis rate, transpiration, and stomatal conductance but decreased the internal concentration of CO2 of leaf. The thickness of the epidermis of the abaxial leaf increased linearly with CS doses, thereby increasing the protective barrier against water stress
Keywords: Cotton; Greenhouse; Growth regulator; Silicate fertilization; Water deficit